Strange vigour a biography of Sun Yat-sen. - Martin, Bernard (Port Washington Kennikat Press, 1970)
The life of a Chinese national hero. Many of the earliest books, particularly those dating back to the 1900s and before, are now extremely scarce and increasingly expensive. Obscure Press are republishing these classic works in affordable, high quality, modern editions, using the original text and artwork.
Originally published in 1944.
Keywords: Sun, Yat-sen, 1866-1925.